CREATIVITY MEASUREMENTS - Fleith, Denise de Souza (2012)
Creativity researchers are often accused of not knowingwhat they are talking about. One of the reasons for this is related to thefact that there are various definitions of creativity, because of the highcomplexity of the construct. As a consequence of this complexity, othersignificam problems appear, such as measurement validity and reliability.The present study discusses the difficulties encountered by creativityresearchers in the definition and measurement of this construct, as wellas the most frequently used creativity measures and their validity andrealibility problems.